Evaluating two different dose frequencies and cumulative intervention intensities to improve past tense production for early school‐aged children with developmental language disorder. Issue 6 (25th August 2021) - Calder, Samuel D.; Claessen, Mary; Leitão, Suze; Ebbels, Susan
Abstract: Aims: This study compared two dose frequency conditions of an explicit intervention with 50 trials per session designed to improve past tense marking in early school‐aged children with developmental language disorder (DLD). The influence of allomorphs on intervention effects was also examined. Methods: Data from previously conducted intervention studies were combined and analysed. Participants included nine children (mean age = 6;5 years) who received 20–30‐min intervention sessions provided twice per week for 10 weeks (1000 trials; 400–600 min) and 20 children (mean age = 6;6) who received 20–30‐min intervention sessions provided once per week for 10 weeks (500 trials; 200–300 min). Repeated measures included criterion‐referenced probes for production of untrained past tense verbs collected throughout baseline, intervention, and maintenance phases. The rate of progress in each phase was analysed using logistic regression. The proportion of participants who produced past tense allomorphs correctly at pre‐intervention, post‐intervention, and maintenance testing points was analysed. Results: Logistic regression showed a stable baseline, highly significant progress during the intervention phase, and a marginally significant shallow decline during the maintenance phase. Those in the twice per week group showed a greater rate of progress during the intervention phase leading to significantly higher scores in the maintenance period when compared with the once per week group. The allomorphic category of past tense verbs did not appear to influence outcomes. Conclusions: Participants receiving intervention twice per week appeared to demonstrate a greater rate of progress with intervention than those receiving it once per week, although once per week was also effective. However, these results should be interpreted with caution. Limitations to study design indicate that a larger randomised controlled trial is required. All past tense allomorphs improve to a similar degree when treated with this intervention. What this paper adds: What is already known on the subject: Understanding the parameters of dosage and intensity are important for clinical practice. Research evaluating the efficacy and/or effectiveness of interventions delivered in different dose/intensity conditions is scarce. There appears to be different interpretations of what constitutes dosage and intensity in published research. What this paper adds to existing knowledge: This study retrospectively compared dosage and intensity conditions of intervention provided twice per week to intervention provided once per week. Both dose frequencies could be delivered in clinical settings. Results from this study were analysed by grouping data from multiple testing points, rather than comparing pre‐post results. This approach demonstrated the variability of individual performance that would otherwise be lost with conventional methods of analysis. This study demonstrated that all past tense allomorphs improve to a similar degree when treated with this intervention. What are the potential or actual clinical implications of this work?: Parameters of dosage and intensity are still not clearly defined well enough for translation to clinical practice. In consideration of current research, this intervention may be more effective if delivered twice per week. If clinicians are treating past tense, all allomorphs should be considered as priorities for intervention targets.